INTEGRATED MODEL OF EDUCATION, DA'WAH, AND SOCIAL ENGAGEMENT: A CASE STUDY OF THE AL AZHAR PARTNERSHIP NETWORK: INTEGRATED MODEL OF EDUCATION, DA'WAH, AND SOCIAL ENGAGEMENT: A CASE STUDY OF THE AL AZHAR PARTNERSHIP NETWORK - Gunanto, Gunanto; Bahar, Herwina; Bahri, Saiful (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
This study investigates the integrative model of formal education, Islamic da’wah, and social engagement within the Al Azhar Islamic Foundation’s partnership network. Using a qualitative multi- case approach, four partner foundations Al Ikhwan, YAPI, Al Hayyan, and Ar-Ridho—were examined to assess how Islamic values are embedded in institutional practice. Data were collected through interviews, observations, documents, and self-assessment tools. Findings show that while all partners adopt Islamic-based educational visions, only a small portion (9%) fully integrate academic, da’wah, and social functions. Innovative programs such as Saung Ilmu, Santri Scholarships, and One Family One Graduate demonstrate how students can engage in both spiritual development and community empowerment. However, integration efforts are often limited by disparities in organizational capacity, funding dependency, and the lack of standardized operational frameworks. The study recommends strengthened governance, staff development, and sustainable financing. This research contributes to the discourse on holistic Islamic education by offering a conceptual model for faith-based educational ecosystems and practical insights for managing Islamic school partnerships effectively.